Comparative study of SSC Cathode Materials for IT-SOFC applications: short review - Roslan, Mohammad Fikrey; Abd Rahman, Hamimah; Abd Karim, Rafidah; Hussin, Mohamed Saiful Firdaus (Academica Press Solutions, 2024)
Solid Oxide Fuel Cells (SOFCs) have the potential to revolutionize the energy landscape with their high efficiency and clean operation. However, a major hurdle lies in their traditional high operating temperatures, which translate to longer startup times and expensive materials. Intermediate-Temperature SOFCs (IT-SOFCs) offer a solution by operating at significantly lower temperatures, but their efficiency relies heavily on the performance of the cathode, the component responsible for the critical oxygen reduction reaction. This review investigates Sm0.5Sr0.5CoO3-δ (SSC) as a promising cathode material for IT-SOFCs due to its inherent activity and compatible thermal expansion. We explore how scientists are pushing the boundaries of SSC performance through various strategies like doping with specific elements, optimizing the internal microstructure, and even creating composites with other materials. By comparing the performance and activity of different modified SSC cathodes reported in recent research, the review sheds light on the most promising approaches. However, challenges remain, including maintaining activity at even lower temperatures and ensuring long-term stability. The future of SSC research lies in addressing these challenges and exploring exciting avenues like identifying new dopants or composite materials. By overcoming these hurdles, SSC has the potential to become a key player in the development of highly efficient and commercially viable IT-SOFCs, paving the way for a cleaner and more sustainable energy future.